PEMANTAUAN PROSES INJEKSI AIR PADA LAPANGAN “SMR” CEKUNGAN SUMATERA TENGAH BERDASARKAN DATA ANOMALI TIME-LAPSE MICROGRAVITY - Ahmad Zaenudin; Dian Pratiwi; Agung Wiyono (Jurnal Geofisika Eksplorasi, 2018)
There had been done a regional research about monitoring of injection process in "SMR" field of Central Sumatera Basin using microgravity method. The time-lapse microgravity method is the development of the gravity method (x, y, z) by adding the fourth dimension of time (t). Monitoring is carried out on production fields that have performed EOR (Enchanced Oil Recovery) ie the process of injecting water into the reservoir to push and drain the remnants of oil in the pores of the reservoir rock to the production well. The microgravity data processing is done by finding the difference between observed gravity values between the first and the second measurements, then performing the spectral analysis to separate the anomaly at reservoir depth and noise. The time-lapse microgravity anomaly has a value of -132.28 μGal to 54.89 μGal. Positive anomalies are related to the injection process, whereas the negative anomalies are related to the production process in the study area. Filtering analysis shows that there are two zones of fluid dynamics, which is due to the process of surface water dynamics (groundwater above reservoir) and that occurs in the reservoir. Fluid reduction zones occur in areas with more production wells than injection wells. Density reduction occurs in the reservoir layer at a depth of 600 m to 1000 m with a maximum reduction value of -3.1x10-3 gr / cm3. The gravity time-lapse inversion model shows the existence of several injection wells that are less effective and therefore need to be stopped injecting.